Recognition and Enforcement of Foreign Arbitral Awards : A Concise Guide to the New York Convention's Uniform Regime /: A Concise Guide to the New York Convention's Uniform Regime. (2023) - Ferrari, Franco; Rosenfeld, Friedrich; Kotuby, Charles T
No abstract available